1968
DOI: 10.1139/v68-541
|View full text |Cite
|
Sign up to set email alerts
|

The mercury (63P1) photosensitized hydrogenation of ethylene. Kinetics of the reaction C2H5 + H2 = C2H6 + H

Abstract: A quantitative study has been made of the reaction of ethyl radicals with molecular hydrogen in the gas phase in the temperature range 240 to 320 "C. The mercury (63P1) photosensitized decomposition of hydrogen in the presence of ethylene was used to generate ethyl radicals. Extinction coefficients for the absorption of 2537 &, by mercury vapor were measured and Beer's law was shown to be obeyed under the experimental conditions used. T h e corrections required to allow for the nonuniformity of radical concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1969
1969
1991
1991

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…Let n' = 116' be the number of collisions of R, * with the inert molecules A necessary for R,'% to obtain energy E,. Because of reaction [9] the number iz = 116 of collisions with C,,H,, molecules necessary to obtain the same energy will be greater than n'. After the R, * radicals have experienced on the average il' collisions, only a fraction (1 -a)"' of these radicals remain unreacted; the necessary number of collisions to transfer an energy AE to the radicals R," becomes n = nf(l -a)-"'.…”
Section: Interpretatiorl Of the Results With The Aid Of Arzmentioning
confidence: 99%
“…Let n' = 116' be the number of collisions of R, * with the inert molecules A necessary for R,'% to obtain energy E,. Because of reaction [9] the number iz = 116 of collisions with C,,H,, molecules necessary to obtain the same energy will be greater than n'. After the R, * radicals have experienced on the average il' collisions, only a fraction (1 -a)"' of these radicals remain unreacted; the necessary number of collisions to transfer an energy AE to the radicals R," becomes n = nf(l -a)-"'.…”
Section: Interpretatiorl Of the Results With The Aid Of Arzmentioning
confidence: 99%
“…largely that by the ratio R(l,,/R(,,+i,. The other terms having only minor significance can then be evaluated and that k-, is equal to that of the analogous reaction of ethyl radical, 10'2.57 exp (-13 7301 RT) cc mole-' s-' (6), and lastly that k -, is equal to exp (-17 730/RT) cc mole-' s-'. Using the recently determined values of k3 and k-, as lo9.'…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Reid and LeRoy (12) concluded tentatively that Ec -Ed = -900 cal mol-' for ethyl radicals in the gas phase, and a paper by James and Suart (13) reported that Ec -Ed = 250 cal mol-' for the mutual interaction of tert-butyl radicals. Konar (14) treated literature data by the thermodynamic formulation of reaction rates, and concluded that Ec is probably not equal to Ed for all alkyl radicals.…”
Section: Ethylene-d4 Solutionsmentioning
confidence: 98%